Photocatalytic Degradation of Methylene Blue using Fe2O3-TiO2/Kaolinite under Visible Light Illumination - Anthoni Batahan Aritonang; Hanopa Selpiana; Muhammad Agus Wibowo; Warsidah warsidah; Adhitiawarman Adhitiawarman (JKPK (Jurnal Kimia dan Pendidikan Kimia), 2022)
Combining TiO2 and a semiconductor with a smaller band gap, such as Fe2O3, to form a heterojunction composite can increase its photocatalytic activity. In this work, the Fe2O3-TiO2/kaolinite composites were successfully synthesized by ultrasonic-assisted coprecipitation using titanium-tetraisopropoxide (TTIP) dan Fe (NO3)3.9H2O as precursors. Using kaolinite as a matrix also increases the photocatalyst’s surface area. The obtained Fe2O3-TiO2/kaolinite composites were characterized. The crystal phase was characterized using X-Ray Diffraction and resulted in anatase with a crystallite size average of 9,7 nm. Fourier Transform Infrared Spectrophotometer (FTIR) shows the peak at a wavenumber 574-1210 cm−1 ascribed TiO2 and Fe2O3 incorporated into kaolinite. The Optical properties show the absorption edge of Fe2O3-TiO2/kaolinite is redshift toward the visible light region. The result showed that the photocatalytic activity of Fe2O3-TiO2/kaolinite composites with heterostructure was more active than the corresponding Fe2O3 or pure TiO2 in the degradation of methylene blue under visible light illumination, which can degrade 83% for 180 minutes. Fe2O3 and kaolinite cause its synergistic effect as supporting materials. Furthermore, it indicates that the recombination of photo hole and photoelectron charge pair can be minimized. The Fe2O3-TiO2/kaolinite composite is a promising photocatalyst to degrade organic pollutants for wastewater treatment.